2022
DOI: 10.1101/2022.02.06.22270558
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Severity and mRNA Vaccine Effectiveness for Omicron, Delta, and Alpha SARS-CoV-2 Variants in the United States: A Prospective Observational Study

Abstract: ObjectivesTo characterize the clinical severity of COVID-19 caused by Omicron, Delta, and Alpha SARS-CoV-2 variants among hospitalized adults and to compare the effectiveness of mRNA COVID-19 vaccines to prevent hospitalizations caused by each variant.DesignA case-control study of 11,690 hospitalized adults.SettingTwenty-one hospitals across the United States.ParticipantsThis study included 5728 cases hospitalized with COVID-19 and 5962 controls hospitalized without COVID-19. Cases were classified into SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 24 publications
3
61
1
Order By: Relevance
“…Full dose vaccination represents 2 doses of BNT162b2, ChAdOx1 nCov-19 and mRNA-1273 vaccines, or 1 dose of Ad26.COV2.S vaccines, whereas booster dose vaccination was defined as the administration of an extra dose of Covid-19 vaccine on top of the full dose vaccination. Two studies 31,37 did not specify the type of vaccines being used; therefore, in this study, we defined it as a mixture. However, it does not necessarily mean that the vaccines are heterologous or mix-and-matched.…”
Section: Resultsmentioning
confidence: 99%
“…Full dose vaccination represents 2 doses of BNT162b2, ChAdOx1 nCov-19 and mRNA-1273 vaccines, or 1 dose of Ad26.COV2.S vaccines, whereas booster dose vaccination was defined as the administration of an extra dose of Covid-19 vaccine on top of the full dose vaccination. Two studies 31,37 did not specify the type of vaccines being used; therefore, in this study, we defined it as a mixture. However, it does not necessarily mean that the vaccines are heterologous or mix-and-matched.…”
Section: Resultsmentioning
confidence: 99%
“…Omicron S has two mutations near the furin cleavage site, N679K and P681H, however the mechanism by which these or other mutations alter S processing remains to be determined. In addition, whether the inefficient use of the metalloproteinase pathway for activation of S to mediate viral entry and cell-cell fusion plays a role in the apparent distinct clinical manifestations and tropism of Omicron is unclear [11,[70][71][72][73]. Nonetheless, our findings of an additional entry pathway suggest a potential for increased tropism in the presence of MMPs during inflammation to cells that do not express serine proteases and could play important roles in dissemination and disease severity.…”
Section: Discussionmentioning
confidence: 95%
“…Some recent studies reported a diminished VE against omicron (B1.1.529) variant COVID-19 infection [ 30 , 31 ] due to the potential for immune evasion, which was supported by in vitro neutralization assays [ 8 , 32 , 33 , 34 ]. In contrast to the VE against the delta variant, the VE against the omicron variant in terms of hospitalization was reportedly lower, at 65% (95% CI: 51–75%), although it remained above 50% [ 35 ]. However, it was reported that the VE against hospitalization improved to 86% (95% CI: 77–91%) after three doses of the vaccine [ 8 , 35 ].…”
Section: Discussionmentioning
confidence: 99%